Kriminalerzählungen der Gegenwart Zur Ästhetik und Ethik einer Leitgattung - Beck, Sandra; Franzen, Johannes (Texturen, 2022)
Contemporary culture is characterised by a peculiar desire for crime narratives. Novels, non-fiction books, films, TV series or podcasts that deal with real or fictional murders, acts of fraud or spectacular thefts attract a wide audience and often become the object of public fascination. The contributions to this volume trace this hunger for crime stories and evaluate both the aesthetic and ethical significance of them having become one of today's leading narrative genres. With contributions by Sandra Beck, Juliane Blank, Johannes Franzen, Peter Hintz, Thomas Kniesche, Till Raether, Oliver Ruf, Simon Sahner, Dana Steglich, Eva Stubenrauch and Thomas Wortmann.